Organizational Justice And Organizational Citizenship Behavior: The Mediating Effect Of Work Satisfaction - Widjajani, Susi (Jurnal Analisis Bisnis Ekonomi, 2021)
This study aims to examine the mediating role of job satisfaction on the effect of organizational justice on organizational citizenship behavior (OCB). The population of this study is the village apparatus in the Village Government in Padureso District, Kebumen Regency with a total of 94 people. The sampling technique uses census techniques in which all members of the population are sampled. Data analysis was performed using Path Analysis. The research instrument used in this study was a questionnaire, which was adopted from several previous studies and had tested its validity and reliability. The results showed that the organizational justice variable had a significant positive effect on job satisfaction, job satisfaction had a significant positive effect on OCB, organizational justice had no significant effect on OCB, but job satisfaction mediated the effect of organizational justice on OCB.